Do Higher Education and Financial Institutions Improve Health in China? A New Perspective - Zhan Zhan; Ran Tao; Muhammad Umer Niaz; Dervis Kirikkaleli (Frontiers Media S.A., 2022)
The importance of human wellbeing is documented in the literature of development economics because of its intensifying impacts on economic growth and productivity of labor in the long-run. To the best of the authors' knowledge, no empirical study has examined the symmetric association between China's financial institutional development, education, and health outcomes. Thus, our study aims to fill this vacuum by employing an autoregressive distributed lag (ARDL) approach to explore the impact of financial institutional development and education on life expectancy and infant mortality rate from 1990 to 2020. The empirical analysis reveals that financial institutional development and education report a significant increase in life expectancy and meaningful reduction in mortality rate in the long-run. Based on these findings, the study may deliver intuitive policy implications regarding improvement in health conditions that are imperative for promoting economic growth in the long-run.